Using Graphic Organizer to Improve Students’ Speaking skill - Rifqi Mahdi Saindra; Mutiarani Mutiarani (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2018)
The purpose of this study was to determine whether Graphic Organizer has a significant effect on students' ability to speak. This study used the VIII.F students of Al-Azhar 12 Junior High School Rawamangun as the research sample. This class consists of 22 students. To choose the sample, the writer used a simple random sampling technique. From the population. The method used in this study was quantitative and the design used was a pre-experimental study with the technique of one group pre and post-test design. The instrument used in this study was oral tests. Then for that reason, the writer used the Weighting Table from Adam and Frith so that the measurement could be more accurate. The result of this research explains that students’ pre-test score is 72,36 and the post-test score is 81,45. The result of statistical hypothesis found out that the level of significance is higher than 0.000 < 0.005. This means H0 (Null Hypothesis) is rejected and H1 (Alternative Hypothesis) is accepted. Which means using the media Graphic Organizer is effective to improve students’ speaking skill.